Analýza nejistot hydrologických a provozních parametrů na vodohospodářské řešení zásobní funkce nádrže - Paseka, Stanislav (Vysoké učení technické v Brně. Fakulta stavební, 2016)
Cílem této práce je představit koncept využití metody Monte Carlo k zavedení nejistot do všech vstupních hydrologických a provozních dat potřebných pro návrh a provoz nádrže. Zavedením nejistot do uvažovaných vstupů vodohospodářského řešení nádrže je následně i vypočtený objem nádrže zatížen nejistotami. Stejně tak jsou zatíženy nejistotami i hodnoty odtoků vody z nádrže a hydrologické zabezpečenosti. Pro výpočty byl použit simulační model chování nádrže, který umožní vyhodnotit výsledky řešení, a tím přispět k redukci nebezpečí vzniku poruchy, respektive nedostatku vody při provozu vodohospodářských nádrží v průběhu málo vodných a suchých obdobích.

The aim of the thesis is to introduce the concept of Monte Carlo method for incorporating the uncertainties into the all hydrological and operational data inputs, which are needed to design and operation of large open water reservoir. Incorporating uncertainties into data inputs during calculation of reservoir storage capacity, then the consequent active conservation storage capacity is loaded by uncertainties. In the same way the values of outflow water from reservoir and hydrological reliability are affected by these uncertainties as well. For these kind of calculations the reservoir simulation model has been used, which simulate behavior operation of reservoir and is able to evaluate the results of simulations and help to reduction risk of storage capacity failure, respectively reduction of water shortages during reservoirs operation during low water and dry periods.
Uncertainty Analysis of Hydrological and Operating Parameters on Water Management Analysis of Reservoir Storage Capacity
Keywords: Nejistota; standardní nejistota; rozšířená nejistota; metoda Monte Carlo; průměrný měsíční průtok; zásobní objem nádrže; simulační model nádrže; zabezpečenost; Uncertainty; Standard Uncertainty; Extend Uncertainty; Monte Carlo Method; Mean Monthly Flows; Reservoir Storage Capacity; Reservoir Simulation Model; Reliability